Hubungan Pengetahuan Remaja Usia 17-20 Tahun Tentang Kesehatan Reproduksi Terhadap Sikap Berpacaran Sehat Di Kelas III SMK 2 Pawyatan Dhaha Kediri - Ira Titisari; Endrastuti Sulistyowati Utami (Akademi Keperawatan Dharma Husada Kediri, 2013)
Social approach with the friends that are shown as serious affair is the stage of growth that adult will experience. This social approach can produce global information that will endanger producing good and qualifying adult. So, knowing and understanding of reproductive health is important to do in order not to make adult have bad attitude and behavior of serious affair. The purpose of this study is to know The Relation of 17-20 year old Adult knowledge About Reroductive Health to The Attitude of Serious Affair in The Third Class of ―SMK 2 pawyatan dhaha‖ Kediri. This study was held on july19 Analitic. The population of this study is all 17-20 year old adults of the third class of ―SMK 2 Pawyatan Dhaha‖ Kediri, they are 223 adults.The sampling technique we use is ―Simple Random Sampling‖, so we get 143 adults as the sample. There are 2 variable, independent variable is the knowledge of 17-20 year old adult about reproductive health and dependent variable is the attitude of serious affair. The variables are measured in the same time with the instrument of study by using questioner. We put the data that we get in a table then we are analized by using Chi Square with So, we can conclude the result of the study , that is ―There are No Relation between the knowledge of 17-20 year old Adult About Reroductive Health to The Attitude of Serious Affair in The Third Class of ―SMK 2 pawyatan dhaha‖ Kediri. Keywords: Knowlwdge, adult, reproductive health, attitude, healthy serious affair